69 Fatigue in Children Before and after Bone Marrow Transplantation: A Preliminary Data. (October 2012) - Petrangeli, F; D'Agostino, F; Sili, A; Petrangeli, T; Alessandrini, S; Alvaro, R
Abstract : Background and aims: Fatigue is described as one of the most frequent and distressing symptoms of cancer therapy but in children and adolescents it has received limited clinical attention. The aim of the study was to assess the change in fatigue scores during cancer treatment according to children's, adolescents' and parents' perspectives and to describe the possible causes of fatigue. Methods: In this longitudinal descriptive study were enrolled 21 patients (aged8–18 years) 15(71%) boys and 6(29%) girls, with acute lymphoblastic (ALL66.6%) and myeloid (AML33.4%) leukemia, and one of their parents. Fatigue as measured by PedsQL Multidimensional Fatigue Scale the day before the first cycle of chemotherapy (T0) and after 30 days (T1) of induction chemotherapy (about 25 days after BMT). Results: Compared data pre and post chemotherapy children had significantly worse fatigue total scores (79.3 DS±10.5vs42.9 DS±8.5, p=0.000): general fatigue domain (77.4DS±14.4vs31.3DS±10.1, p=0.000), sleep/rest fatigue domain (73.4DS±15.8vs28.6DS±12.1, p=0.000), and cognitive fatigue was the better and similar domain pre and after BMT in child's (87.1DS±11.2vs69DS±17.5, p=0.000) and parents' (88.3DS+12vs68.2DS±21.4) perception. Children with ALL (41.7DS±8.9) had a worse fatigue than AML (45.6DS±7.6) and the fatigue parent's perception about their children is worse than child's perception (38.2vs42.9). Conclusions: This study shown that cancer treatment increase significantly children's fatigue levels. Nurses should frequently assess fatigue in children receiving chemotherapy and apply timely and tailored interventions to match the factors that contribute to fatigue and influence fatigue severity, further to identify the domains compromises and make correct nursing diagnoses. Management of fatigue during treatment will help children stay involved in age-related activities and meet developmental milestones.